An international stratigraphic dataset and geological map of the Ahr River catchment, Germany - Svenja Scholz; Henriette Westermann; Ronja Hegemann; Mara Popp; Tobias Richter; Markus L. Fischer; Christoph Zielhofer (Data in Brief, 2023)
This dataset provides detailed chronostratigraphic and lithological maps of the entire Ahr River catchment, which is located in Western Germany. The geological information was acquired using a transfer of the German chronostratigraphic terms into the international stratigraphic notation. Information about the geology and lithology was provided by publicly sourced data released by the German federal states North Rhine-Westphalia and Rhineland-Palatinate. The dataset includes information about the international stratigraphy, the corresponding German unit, and the lithology in English and German. The dataset is essentially useful for catchment-scale research, for example with regard to the causes and consequences of the July 2021 flooding of the Ahr River.